Endoscopic Submucosal Dissection for Early Colorectal Neoplasms: Clinical Experience in a Tertiary Medical Center in Taiwan. (25th February 2013) - Tseng, Mei-Yu; Lin, Jung-Chun; Huang, Tien-Yu; Shih, Yu-Lueng; Chu, Heng-Cheng; Chang, Wei-Kuo; Hsieh, Tsai-Yuan; Chen, Peng-Jen
Abstract : Objectives . Endoscopic submucosal dissection (ESD) is a promising technique to treat early colorectal neoplasms by facilitating en bloc resection without size limitations. Although ESD for early gastrointestinal epithelial neoplasms has been popular in Japan, clinical experience with colorectal ESD has been rarely reported in Taiwan. Methods . From March 2006 to December 2011, 92 consecutive patients with early colorectal neoplasms resected by ESD at Tri-Service General Hospital were included. ESD was performed for colorectal epithelial neoplasms with a noninvasive pit pattern which had the following criteria: (1) lesions difficult to remove en bloc with a snare, such as laterally spreading tumors-nongranular type (LST-NG) ≧20 mm and laterally spreading tumors-granular type (LST-G) ≧30 mm; (2) lesions with fibrosis or which had recurred after endoscopic mucosal resection with a nonlifting sign. Results . The mean age of the patients was 66.3 ± 12.9 years, and the male-female ratio was 1.8 : 1. The mean tumor size was 37.2 ± 17.9  mm. The en bloc resection rate was 90.2% and the R0 resection rate was 89.1%. Perforations during ESD occurred in 11 patients (12.0%) and all of them were effectively treated by endoscopic closure with hemoclips. No delayed perforation or postoperative bleeding was recorded. There were no procedure-related morbidities or mortalities. Conclusion . ESD is an effective method for en bloc resection of large early colorectal neoplasms and those with a nonlifting sign. An endoscopic technique to close perforations is essential for colorectal ESD.